The Influence of Audit Staff Quality and Client Type on Audit Evidence Collection with Communication Type as Moderation - Syamsuri Rahim; Hamzah Ahmad; Nurwakia Nurwakia; Nurfadila Nurfadila; Muslim Muslim (Journal of Accounting and Strategic Finance, 2020)
This study aims to examine the effect of audit staff quality (staff in-charge or auditors who carry out audit tasks) and the client type on the audit evidence collection is moderated by the communication type. The study population was auditors working in the Makassar Public Accounting Firm. The sampling technique used was purposive sampling, while the data collection was done by distributing questionnaires to all auditors who met the sample criteria. The samples are thirty-three auditors from seven public accountant office in Makassar city. The hypothesis test was conducted using Smart PLS 3. This study found that the audit staff quality, client type, and communication type had a positive effect on the collection of audit evidence directly. Furthermore, the moderation test results found that the communication type strengthens the relationship between the client type and the collection of audit evidence. It means that while gathering audit evidence, the higher the audit staff quality, the more evidence they can obtain. The same result also found in the relationship between the client type and the audit evidence collection. When the client type is friendly, the more audit evidence is gathered. Based on these results, it is suggested that junior auditor must build their confidence in dealing with the clients.